2020
DOI: 10.1371/journal.pone.0239604
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into the effect of compliance of a mock aorta on cardiac performance

Abstract: Demand for heart transplants far exceeds supply of donated organs. This is attributed to the high percentage of donor hearts that are discarded and to the narrow six-hour time window currently available for transplantation. Ex-vivo heart perfusion (EVHP) provides the opportunity for resuscitation of damaged organs and extended transplantation time window by enabling functional assessment of the hearts in a near-physiologic state. Present work investigates the fluid mechanics of the ex-vivo flow loop and corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…However, such aorta compliance feature is not currently involved in the EVHP system because its hydraulic circuit is essentially composed of rigid tubes. In a previous work, it was shown that the use of a compliant tube, mimicking the aorta, instead of a rigid tubing in the EVHP system's flow loop could alter the flow-pressure relationship of the pulsatile flow, making it more similar to the physiological profile and also reducing the workload of the heart [19]. However, this study was conducted with only a single compliant tube.…”
Section: Introductionmentioning
confidence: 99%
“…However, such aorta compliance feature is not currently involved in the EVHP system because its hydraulic circuit is essentially composed of rigid tubes. In a previous work, it was shown that the use of a compliant tube, mimicking the aorta, instead of a rigid tubing in the EVHP system's flow loop could alter the flow-pressure relationship of the pulsatile flow, making it more similar to the physiological profile and also reducing the workload of the heart [19]. However, this study was conducted with only a single compliant tube.…”
Section: Introductionmentioning
confidence: 99%